Endogenous d-serine exists in the mammalian brain independent of synthesis by serine racemase - Osaki, Akina; Aoyama, Marie; Mita, Masashi; Hamase, Kenji; Yasui, Masato; Sasabe, Jumpei (Biochemical and biophysical research communications, 2023)
Activation of N-methyl-d-aspartate receptors (NMDARs) requires binding of a co-agonist in addition to l-glutamate. d-serine binds to the co-agonist site on GluN1 subunits of NMDARs and modulates glutamatergic neurotransmission. While loss of GluN1 subunits in mice results in neonatal death due to respiratory failure, animals that lack a d-serine synthetic enzyme, serine racemase (SR), show grossly normal growth. However, SR-independent origins of d-serine in the brain remain unclarified. In the present study, we investigated the origin of brain d-serine in mice. Loss of SR significantly reduced d-serine in the cerebral cortex, but a portion of d-serine remained in both neonates and adults. Although d-serine was also produced by intestinal bacteria, germ-free experiments did not influence d-serine levels in the cerebral cortex. In addition, treatment of SR-knockout mice with antibiotics showed a significant reduction of intestinal d-serine, but no reduction in the brain. On the other hand, restriction of dietary intake reduced systemic circulation of d-serine and resulted in a slight decrease of d-serine in the cerebral cortex, but did not account for brain d-serine found in the SR-knockout mice. Therefore, our findings show that endogenous d-serine of non-SR origin exists in the brain. Such previously unrecognized, SR-independent, endogenous d-serine may contribute baseline activity of NMDARs, especially in developing brain, which has minimal SR expression. •Mammalian brain contains d-serine unoriginated from serine racemase throughout life (83).•d-serine production by symbiotic microbes has no contribution to brain d-serine level (85).•Non-dietary d-serine derived not from serine racemase exists in the brain (73).